Special Exercises For Developing Hurdle Stride In Different Phases Of Youth 400m Hurdles - Mohameed, Ahmed; Kazem, Hasnaa (Journal of Physical Education, 2016)
The problem of the research lies in the special endurance weakness in manyyouth hurdlers that leads to great decline in achievement, the researchers hypothesizedstatistical difference in pre and posttests in special endurance. The researcher used theexperimental method. The subjects were (6) youth hurdles. The researcher selected manytests; 150m hurdles test, 200m hurdles test, and 300m hurdles test to measure special speedendurance. Pretests were conducted followed by the training program. The training programconsisted (8) weeks with (3) training sessions per week. After posttests, the data wascollected and treated using proper statistical methods. The results showed that special speedendurance training lead to the development of some special physical abilities as well ashurdle stride in the third, fifth, and eighth hurdles. The training program developed the strideperformance level in youth hurdlers in 150m, 200m, and 300m hurdles.